Implication of LAMP proteins and autophagy markers in colorectal cancer aggressiveness - Ivanova, Tsvetomira; Dikov, Dorian; Molander, Diana; Dzhambov, Angel M.; Sbirkov, Yordan; Mehterov, Nikolay; Belev, Nikolay; Atanasov, Boyko; Kazakova, Maria; Sarafian, Victoria (Frontiers in Immunology, 2025)
Lysosome-associated membrane proteins (LAMPs) play a critical role in various cellular processes, including phagocytosis, lipid transport, neoangiogenesis, and tissue remodeling. Recent discussions have focused on their involvement in autophagy related to tumor progression. Emerging studies have underscored the connection between tumorigenesis and autophagy, highlighting that dysregulation of this process is associated with the resistance of tumor cells to conventional chemotherapy across numerous malignancies, including colorectal cancer (CRC). Currently, there is a notable absence of reliable prognostic biomarkers for effectively stratifying and predicting treatment responses in CRC patients. Our study examines the expression of LAMP1 and LAMP2 proteins and genes alongside key autophagy markers such as BECLIN1 and LC3B, investigating their relationships with CRC invasiveness. We present original data illustrating the association of LAMP molecules with standard autophagy markers and tumor budding. Our findings provide novel insights into the significance of these markers in CRC invasiveness, their relationship with survival rates, and their potential role as prognostic biomarkers.